Application of knockdown technology for wooden bow arch bridges - Insan Kamil; Rafian Tistro; Salma Alwi; Dhiana DW (Community Empowerment, 2021)
The use of wood as a construction material for simple bridges has begun to be abandoned and switch to concrete or steel bridges with considerations of durability and structural strength. However, from an ecological perspective, wood is still the most renewable material by nature itself. Returning to ecologic natural materials is an issue of the United Nation that needs to be supported by educational institutions. This community service begins with determining the span and height of the bridge, followed by planning and calculating the strength of the material. The parts of the bridge are manufactured in the workshop of the Civil Engineering Department, Samarinda State Polytechnic. The assembly and erection processes are carried out in the field. The uniqueness of this program is in the application of the wooden arc bridge model with a raft unloading system by presenting an attractive aesthetic, so that it is hoped that it can again become an option in determining the type of bridge for users.